Meeting of law enforcement science and frontier-guard mentality – no future without past (Academic Journal of Internal Affairs, 2020)
The author gives an overview in the 20th jubilee edition of the Scientific Announcement of the Pécs Border Guard, beside news of law enforcement science, about the values of the organisational culture of the border protection organisations gained in a process of several decades. The author articulates his professional ideas about keeping traditions, organisational culture, and mentality of border guards.
Keywords: police sciences; border guard services; Hungary